Acute intravascular haemolysis and renal failure due to arsine poisoning. Issue 521 (March 1969) - Coles, G. A.; Davies, H. J.; Daley, D.; Mallick, N. P.
Abstract : Two men developed acute intravascular haemolysis after exposure to arsine gas in a metal smelting works. Both survived; one developed acute renal failure and required peritoneal dialysis. His renal function returned to near normal within 3 months. The probable mode of exposure has been investigated and is discussed. The toxic effects of arsine are briefly reviewed. The preventive action taken is detailed.